Efficacy and tolerability of Guizhi-Shaoyao-Zhimu decoction in gout patients: a systematic review and Meta-analysis - Qing Zhang; Ruolan Li; Jia Liu; Wei Peng; Wenxiang Fan; Yongxiang Gao; Wei Jin; Chunjie Wu (Taylor & Francis Group, 2020)
Context Guizhi-Shaoyao-Zhimu decoction (GSZD), a famous ancient oriental Chinese prescription, has been widely used for thousands of years to treat 'arthromyodynia'. Objective The clinical studies of GSZD for the treatment of gout were systematically reviewed to evaluate its clinical efficacy and safety. Methods All randomized controlled trials (RCTs) related to GSZD and gout were collected starting from the database establishment until 29 February 2020, from the Embase, PubMed, Cochrane Library, Web of Knowledge, VIP and other databases. This systematic review and meta-analysis were performed in strict accordance with the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analysis) statement, and all analysis of the test was completed using Stata (SE12.0) and Revman (5.3). Results A total of 535 studies were searched, and 13 studies were included in our meta-analysis (n = 1056 participants). Compared with the conventional western medicine treatments, GSZD treatment yielded a significantly increase in the number of clinically effective patients (OR = 3.67, 95%CI = 2.39-5.64, p = 0.57), an improved mean reduction in the level of uric acid (MD = −54.06; 95% CI = −69.95 to −38.17). Meanwhile, the levels of erythrocyte sedimentation rate (ESR), C-reactive protein (CRP) and interleukin-6 (IL-6) were also significantly decreased after the GSZD treatment with no increased relative risk of side-effects. Conclusions Our present works suggested that GSZD could be considered as an effective alternative remedy for clinical treatment of gout. In addition, it also provides a scientific basis for GSZD to be better applied in clinic in the future.